Construction of Ocean Blue Resort, Sunut Jerowaru; Local Community Perspectives - Dani Alfatwari; Parham; Muh Hilmi Pauzi; Muhammad Adi Junaidi (JMET: Journal of Management Entrepreneurship and Tourism, 2023)
The purpose of this study is to determine public perceptions or opinions related to the development of ocean blue companies. This research was conducted in Pemongkong Village, Jerowaru District, East Lombok Regency starting from January 7 to April 7, 2012. Based on the results of research and the results of data analysis that has been carried out, various perceptions are obtained from the community but still focus on one problem that is important and important and does not go out of the corridor that has been determined. Data collection techniques use frequency distribution techniques, the method used is data processing, data processing is adjusted to the needs of the analysis being done. The analytical techniques used by researchers in this study are descriptive quantitative data analysis techniques and data sources through primary data, namely data obtained from respondents through direct interviews guided by questionnaires (lists of questions) and using secondary data in the form of archives, documents or other written evidence obtained by researchers from Pemongkong Village directly. The results of this study can show the characteristics of respondents who became respondents in this study were the people of Pemongkong Village, Jerowaru District, East Lombok Regency who then obtained samples from this study as many as 38 people.